A correlation between lipid domain shape and binary phospholipid mixture composition in free standing bilayers: A two-photon fluorescence microscopy study. - Bagatolli, L A (2000)
Giant unilamellar vesicles (GUVs) composed of different phospholipid binary mixtures were studied at different temperatures, by a method combining the sectioning capability of the two-photon excitation fluorescence microscope and the partition and spectral properties of 6-dodecanoyl-2-dimethylamino-naphthalene (Laurdan) and Lissamine rhodamine B 1,2-dihexadecanoyl-sn-glycero-3-phosphoethanolamine (N-Rh-DPPE). We analyzed and compared fluorescence images of GUVs composed of 1,2-dilauroyl-sn-glycero-3-phosphocholine/1, 2-dipalmitoyl-sn-glycero-3-phosphocholine (DLPC/DPPC), 1, 2-dilauroyl-sn-glycero-3-phosphocholine/1, 2-distearoyl-sn-glycero-3-phosphocholine (DLPC/DSPC), 1, 2-dilauroyl-sn-glycero-3-phosphocholine/1, 2-diarachidoyl-sn-glycero-3-phosphocholine (DLPC/DAPC), 1, 2-dimyristoyl-sn-glycero-3-phosphocholine/1, 2-distearoyl-sn-glycero-3-phosphocholine (DMPC/DSPC) (1:1 mol/mol in all cases), and 1,2-dimyristoyl-sn-glycero-3-phosphoethanolamine/1, 2-dimyristoyl-sn-glycero-3-phosphocholine (DMPE/DMPC) (7:3 mol/mol) at temperatures corresponding to the fluid phase and the fluid-solid phase coexistence. In addition, we studied the solid-solid temperature regime for the DMPC/DSPC and DMPE/DMPC mixtures. From the Laurdan intensity images the generalized polarization function (GP) was calculated at different temperatures to characterize the phase state of the lipid domains. We found a homogeneous fluorescence distribution in the GUV images at temperatures corresponding to the fluid region for all of the lipid mixtures. At temperatures corresponding to phase coexistence we observed concurrent fluid and solid domains in the GUVs independent of the lipid mixture. In all cases the lipid solid domains expanded and migrated around the vesicle surface as we decreased the temperature. The migration of the solid domains decreased dramatically at temperatures close to the solid-fluid-->solid phase transition. For the DLPC-containing mixtures, the solid domains showed line, quasicircular, and dendritic shapes as the difference in the hydrophobic chain length between the components of the binary mixture increases. In addition, for the saturated PC-containing mixtures, we found a linear relationship between the GP values for the fluid and solid domains and the difference between the hydrophobic chain length of the binary mixture components. Specifically, at the phase coexistence temperature region the difference in the GP values, associated with the fluid and solid domains, increases as the difference in the chain length of the binary mixture component increases. This last finding suggests that in the solid-phase domains, the local concentration of the low melting temperature phospholipid component increases as the hydrophobic mismatch decreases. At the phase coexistence temperature regime and based on the Laurdan GP data, we observe that when the hydrophobic mismatch is 8 (DLPC/DAPC), the concentration of the low melting temperature phospholipid component in the solid domains is negligible. This last observation extends to the saturated PE/PC mixtures at the phase coexistence temperature range. For the DMPC/DSPC we found that the nonfluorescent solid regions gradually disappear in the solid temperature regime of the phase diagram, suggesting lipid miscibility. This last result is in contrast with that found for DMPE/DMPC mixtures, where the solid domains remain on the GUV surface at temperatures corresponding to that of the solid region. In all cases the solid domains span the inner and outer leaflets of the membrane, suggesting a strong coupling between the inner and outer monolayers of the lipid membrane. This last finding extends previous observations of GUVs composed of DPPE/DPPC and DLPC/DPPC mixtures (, Biophys. J. 78:290-305).